Uncles and Aunts by Vaižgantas in Literary History, Cinema and Theatre - Vanagaitė, Gitana (Colloquia, 2018)
In the article, by combining several theoretical accesses (narratology, intermediality and hermeneutics), the author analyzes Uncles and Aunts (Dėdės ir dėdienės) – the long story by Vaižgantas which is accounted for literary classics, and also its theatre and cinema versions: the film That Cursed Humility (Tas prakeiktas nuolankumas) and two theatre productions of the same title. She raises the following questions: what kind of canon of reading and comprehending Vaižgantas’ story has been circulating in the culture circle, and how have the film and performances been affecting this canon? Another question in the article is related to the relations between literary / cinema / theater texts. Both the film and theatre performances have explicit references to the story by Vaižgantas, as if recognizing the original, or authorly, status of this story. However, in spite of the relationship establishing this hierarchy, the film version and theatre productions, which took place in different historical-political times, regarded the ideological specificity of their times rather than the axiological plane of the story that claims versatility (except the production directed by Regina Steponavičiūtė). Perhaps, that is why today there is still no solid canon of reading / comprehending Uncles and Aunts, which would be required by the literary classics standard. On the one hand, this proves the openness and versatility of the messages of the story by Vaižgantas, which is strongly related to the specificities of a certain period of time – the serfdom. On the other hand, this once again questions the concept of dialogue proposed by adaptation theories, on the basis of which the artistic hierarchy should be rejected and the cinema / theatre text perceived independently.